Efektifitas Terapi Aroma Bunga Lavender (Lavandula Angustifolia) terhadap Penurunan Skala Nyeri pada Klien Infark Miokard - Dasna ' '; Gamya Tri Utami; Arneliwati ' ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract This study aimed to determine the effectiveness of aroma therapy lavender flowers (Lavandula angustifolia) to decrease pain scale client myocardial infarction. Design of the study was Quasi- Experimental with Pre test and post test desain with control group were divided into experimental group and control group. The study was conducted on clients who have pain with nursing diagnosis of myocardial infarction in the Cardiovascular Care Unit ( CVCU ) Arifin Achmad Pekanbaru hospital. The number of samples were 30 people, consist of 15 in the experimental group and 15 control group by purposive sampling with the inclusion criteria. Measuring instrument used the observation sheet Descriptive Pain Scale (Descriptive Verbal Scale). The experimental group was given treatment with lavender aroma therapy by inhalation. The analysis used univariate and bivariate with Mann-Whitney test and Wilcoxon test. The results showed a significant difference intensity scale pain scores between the experimental group and the control group with p value 0.009 (p value <0.05), which means aromatherapy lavender (Lavandula angustifolia) is effective in reducing pain intensity scale on the client myocardial infarction. Researchers suggest that administration of lavender aroma therapy can be applied to clients with experience pain myocardial infarction in hospitals and in the community. Keywords : Therapy Lavender Flowers, painful, myocardial infarction